A Multi-faceted Approach to Promote Comprehension of Online Health Information Among Older Adults. (10th March 2017) - Chin, Jessie; Moeller, Darcie D; Johnson, Jessica; Duwe, Elise A G; Graumlich, James F; Murray, Michael D; Morrow, Daniel G
Abstract: Purpose of the Study: Older adults' self-care often depends on understanding and utilizing health information. Inadequate health literacy among older adults poses a barrier to self-care because it hampers comprehension of this information, particularly when the information is not well-designed. Our goal was to improve comprehension of online health information among older adults with hypertension who varied in health literacy abilities. Design and Methods: We identified passages about hypertension self-care from credible websites ( typical passages). We used a multi-faceted approach to redesign these passages, revising their content, language, organization and format ( revised passages). Older participants read both versions of the passages at their own pace. After each passage, they summarized the passage and then answered questions about the passage. Results: Participants better remembered the revised than the typical passages, summarizing the passages more accurately and uptaking information more efficiently (less reading time needed per unit of information remembered). The benefits for reading efficiency were greater for older adults with more health knowledge, suggesting knowledge facilitated comprehension of information in the revised passages. Implications: A systematic, multi-faceted approach to designing health documents can promote online learning among older adults with diverse health literacy abilities.